Rotavirus A in Brazil: Molecular Epidemiology and Surveillance during 2018-2019 - Gutierrez, Meylin Bautista (2020)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Virologia Comparada e Ambiental. Rio de Janeiro, RJ, Brasil.